2017
DOI: 10.15420/icr.2017:25:1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding neurologic complications following TAVI

Abstract: Transcatheter aortic valve replacement is a groundbreaking treatment modality for severe, symptomatic aortic stenosis. Despite the rapid progression in indications to include intermediate-risk patients, the risk of peri-procedural stroke remains, with a higher incidence rate than previously reported. Accurate assessment of peri-procedural stroke rates requires selection of careful and meaningful trial endpoints during evaluation of neuroprotective devices. In this article, we review recommendations and stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Use of DW-MRI as an additional diagnostic tool in patients with lower rSO 2 values can increase earlier detection of NCs and better management of patients. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Use of DW-MRI as an additional diagnostic tool in patients with lower rSO 2 values can increase earlier detection of NCs and better management of patients. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous post-TAVR cerebral MRI studies reported a higher ischemic brain lesion volume of 1.5 to 4.3cm 3 in up to 77% of patients, if compared with our results in a low surgical risk population. 1 Potential limitations of this study may be the small sample size, a change in the medical regimen in patients with new-onset AF, and a heterogeneity of procedures (several valve-in-valve procedures, use of protection devices in some patients).…”
mentioning
confidence: 98%
“…1 The mechanism of cerebral embolism may differ according to the early time period (procedure related within 48 hours of TAVR), or later (nondirectly procedure related, eg, atrial fibrillation [AF] or valve leaflet thrombosis). 1 In the PARTNER trial (The Placement of Aortic Transcatheter Valves), 62.5% of the major strokes occurred within the first 48 hours post-TAVR, 25% between days 5 and 30, and 1 stroke was noted after the first month. 2 Mobilization of debris from the calcified native aortic valve or the aorta during the implant procedure may explain a significant proportion of early strokes.…”
mentioning
confidence: 99%
See 2 more Smart Citations